Experimental Exploration of Objective Human Pain Assessment Using Multimodal Sensing Signals - Lin, Yingzi; Xiao, Yan; Wang, Li; Guo, Yikang; Zhu, Wenchao; Dalip, Biren; Kamarthi, Sagar; Schreiber, Kristin L.; Edwards, Robert R.; Urman, Richard D. (Frontiers in Neuroscience, 2022)
Optimizing pain assessment and treatment is an active area of research in healthcare. The purpose of this paper is to create an objective pain intensity estimation system based on multimodal sensing signals through experimental studies. 28 healthy subjects were recruited at Northeastern University. Nine physiological modalities were utilized in this research, namely facial expressions (FE), electroencephalography (EEG), eye movement (EM), skin conductance (SC), and blood volume pulse (BVP), electromyography(EMG), respiration rate (RR), skin temperature (ST), blood pressure (BP). Statistical analysis and machine learning algorithms were deployed to analyze the physiological data. FE, EEG, SC, BVP, and BP proved to be able to detect different pain states from healthy subjects. Multi-modalities proved to be promising in detecting different levels of painful states. A decision-level multi-modal fusion also proved to be efficient and accurate in classifying painful states.